2002
DOI: 10.1590/s1415-47572002000200008
|View full text |Cite
|
Sign up to set email alerts
|

Genetic components affecting embryonic developmental time of Drosophila melanogaster

Abstract: The developmental time of the embryonic stage of Drosophila melanogaster was 21.66% faster and 14.75% slower than controls in populations selected for fast and slow developmental speed, respectively. The genetic model with two main loci with dominant and additive effect added to maternal effect and their relevant interactions can explain 96% of the phenotypic variability in the embryonic developmental time according to 14 crossing progenies involving fast and slow flies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…During insect development, larval pattern building and metamorphosis are considered as two different developmental processes that contribute to the formation of adults (Nascimento et al, 2002). It is known that the developmental time of each preimaginal stage, including the embryonic period (phase), regulates the time needed for body development, fitting the developmental time into the environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…During insect development, larval pattern building and metamorphosis are considered as two different developmental processes that contribute to the formation of adults (Nascimento et al, 2002). It is known that the developmental time of each preimaginal stage, including the embryonic period (phase), regulates the time needed for body development, fitting the developmental time into the environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, as Phelan et al (2003) have shown, the correlations between functional characters are not necessarily durable features of a species, and short-term evolutionary responses cannot be extrapolated reliably to longerterm evolutionary patterns. Also, flies' developmental time may show high plasticity in insects living in unstable environments, as each preimaginal stage during insect development plays a role in the regulation of time needed for body development (genetic pattern) and in fitting developmental time to environmental conditions (phenotype plasticity) (do Nascimento et al, 2002). Table A2.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the environmental factor (high temperature) and experience (diapause or not) in the parent, genetic differences may also be attributed to these. do Nascimento et al (2002) did reported genetic components affected development time in Drosophila melanogaster. However, our understanding of the molecular regulation of diapause remains in its infancy (Denlinger, 2002).…”
Section: Discussionmentioning
confidence: 99%